Overall Equipment Effectiveness (OEE) Analysis to Minimize Six Big Losses in Continuous Blanking Machine - Bintang Fadhilah Putri Aulia Marfinov; Ahmad Juang Pratama (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2020)
This paper describes the high downtime on continuous blanking machines. The result is that companies suffer losses in cost, human resources, and time. Therefore, companies need to implement Total Productive Maintenance (TPM). TPM aims to improve the overall efficiency and effectiveness of manufacturing companies. Then the TPM itself needs to be evaluated. One of the methods used is the Overall Equipment Effectiveness (OEE) as an indicator of the machine's effectiveness by calculating the six big losses to determine the factors that influence the six factors of the six big losses. Based on research that has been done, the machine availability ratio is 99%, performance efficiency is 84%, product rate of quality is 83%. While the value obtained on the OEE calculation is 71%, the value is below the world's ideal OEE standard value of > 85%. The highest loss values for six big losses are idle and minor stoppage losses with a percentage of 62.73%, setup and adjustment losses of 14.38%.